Citrus leprosis virus C Infection Results in Hypersensitive-Like Response, Suppression of the JA/ET Plant Defense Pathway and Promotion of the Colonization of Its Mite Vector - Arena, Gabriella D.; Ramos-González, Pedro L.; Nunes, Maria A.; Ribeiro-Alves, Marcelo; Camargo, Luis E. A.; Kitajima, Elliot W.; Machado, Marcos A.; Freitas-Astúa, Juliana (Frontiers in Plant Science, 2016)
Leprosis is a serious disease of citrus caused by Citrus leprosis virus C (CiLV-C, genus Cilevirus) whose transmission is mediated by false-spider mites of the genus Brevipalpus. CiLV-C infection does not systemically spread in any of its known host plants, thus remaining restricted to local lesions around the feeding sites of viruliferous mites. To get insight into this unusual pathosystem, we evaluated the expression profiles of genes involved in defense mechanisms of Arabidopsis thaliana and Citrus sinensis upon infestation with non-viruliferous and viruliferous mites by using reverse transcriptase-qPCR. These results were analyzed together with the production of reactive oxygen species (ROS) and the appearance of dead cells as assessed by histochemical assays. After interaction with non-viruliferous mites, plants locally accumulated ROS and triggered the salicylic acid (SA) and jasmonate/ethylene (JA/ET) pathways. ERF branch of the JA/ET pathways was highly activated. In contrast, JA pathway genes were markedly suppressed upon the CiLV-C infection mediated by viruliferous mites. Viral infection also intensified the ROS burst and cell death, and enhanced the expression of genes involved in the RNA silencing mechanism and SA pathway. After 13 days of infestation of two sets of Arabidopsis plants with non-viruliferous and viruliferous mites, the number of mites in the CiLV-C infected Arabidopsis plants was significantly higher than in those infested with the non-viruliferous ones. Oviposition of the viruliferous mites occurred preferentially in the CiLV-C infected leaves. Based on these results, we postulated the first model of plant/Brevipalpus mite/cilevirus interaction in which cells surrounding the feeding sites of viruliferous mites typify the outcome of a hypersensitive-like response, whereas viral infection induces changes in the behavior of its vector.